Social entrepreneurship: Business models and strategies for their development - Ayaganova, M.; Pritvorova, T.; Mamrayeva, D.; Tashenova, L. (Economic Annals-XXI, 2019)
The authors conducted the research of business models in social entrepreneurship. Firstly, the foreign experience of business models implementation by successful companies in global economy was studied and among 55 innovation models 8 business model types which can be used by social entrepreneurs were singled out. On this basis, the methodical approaches to the design of business models and their development strategies on the example of the Republic of Kazakhstan were developed. In particular, the main characteristics of the business model of social entrepreneurship are deepened and disclosed from the standpoint of the nature of impact on the socially vulnerable groups’ welfare. The main types of social entrepreneurship and the business models applied in Kazakhstan were revealed. Taking into account the results of in-depth interview of 24 social entrepreneurship organizations, the business models applied by non-commercial organizations in Kazakhstan for development of profitable activity were found out, namely: No. 1 - «Accessibility of product/service in case of standard offer»; No. 2 - «Additional income from cheap resources and available IT (creation and promotion of side products)»; joint models No. 1 - «Accessibility of product/service in case of standard offer» and No. 5 - «Maximum assets utilization»; and No. 3 - «Platform for contacts, including auction and crowdfunding». Based on strategic analysis of social entrepreneurship at non-profit as well as commercial organizations, conclusions were drawn about the threats / limitations and the possibilities of existing business models. An algorithm has been developed to design a business model of social entrepreneurship and a strategy for developing business models. Strategic development scenarios of business models of social entrepreneurship were proposed, namely: scalability of operation; replication of operation; modification of the business model; creation of cooperating structures.
Keywords: Social Entrepreneurship; Social Enterprises; Socially Responsible Business; Business Models; Development Strategies